Slovak Republic : Financial System Stability Assessment Update, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Insurance Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents the Slovak Republic's Financial System Stability Assessment Update including Reports on the Observance of Standards and Codes on Banking Supervision and Insurance Regulation. Commercial banks are by far the dominant financial institutions, though nonbank financial institutions have grown faster than banks in recent years, and the securities markets remain small. Although rapid, the rate of bank credit growth seems appropriate, given the strong outlook for the economy. Stress tests confirm that banks are currently resilient to a range of possible adverse shocks.